2021
DOI: 10.3390/cells10010145
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 and Superantigenic Activation of Human Lung Mast Cells Induce the Release of Angiogenic and Lymphangiogenic Factors

Abstract: Human lung mast cells (HLMCs) express the high-affinity receptor FcεRI for IgE and are strategically located in different compartments of human lung, where they play a role in several inflammatory disorders and cancer. Immunoglobulin superantigens (e.g., protein A of Staphylococcus aureus and protein L of Peptostreptococcus magnus) bind to the variable regions of either the heavy (VH3) or light chain (κ) of IgE. IL-33 is a cytokine expressed by epithelial cells that exerts pleiotropic functions in the lung. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 160 publications
1
40
0
1
Order By: Relevance
“…Angiogenesis, the formation of new blood vessels, is a complex process modulated by a plethora of stimulatory and inhibitory factors [85,86]. There is some evidence the angiogenic switch in asthmatic airways involves the production of direct (e.g., VEGFs, angiopoietins) and indirect angiogenic factors (e.g., MMP-9, cysteinyl leukotrienes) [86,114,115]. Interestingly, the plasma concentrations of VEGF-A, which is also released by activated human PMNs [88,89], were similar in asthmatic and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis, the formation of new blood vessels, is a complex process modulated by a plethora of stimulatory and inhibitory factors [85,86]. There is some evidence the angiogenic switch in asthmatic airways involves the production of direct (e.g., VEGFs, angiopoietins) and indirect angiogenic factors (e.g., MMP-9, cysteinyl leukotrienes) [86,114,115]. Interestingly, the plasma concentrations of VEGF-A, which is also released by activated human PMNs [88,89], were similar in asthmatic and controls.…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF is considered a key orchestrator of neutrophil involvement in chronic airway inflammation [83,84]. VEGF-A, the most important angiogenic factor [85][86][87], is produced by activated human neutrophils [66,88,89]. Figure 4 shows that the plasma levels of MPO, MMP-9 and CXCL8 were significantly increased in asthmatics compared to healthy donors.…”
Section: Plasma Levels Of Neutrophil-derived Mediatorsmentioning
confidence: 99%
“…The production of TSLP by HLMs suggested to us possible autocrine effects on these cells which are the most representative immune cells in human lung parenchyma [71,107]. We found that HLMs incubated with TSLP released significant amount of proinflammatory TNF-α and of several angiogenic (i.e., VEGF-A and ANGPT2) [108,109] and lymphangiogenic molecules (i.e., VEGF-C) [110,111]. These findings were supported by the observation that TSLP markedly increased the expression of TNF-α, VEGF-C, ANGPT2 mRNAs.…”
Section: Discussionmentioning
confidence: 69%
“…All the previously mentioned mediators play pivotal roles in tumor initiation and progression, tumor angiogenesis, and the formation of metastasis [109,112]. These results prompted us to investigate the expression of TSLP system in human lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several other immune cells (e.g., macrophages, mast cells, neutrophils, ILC3, T H 1 cells, plasma cells) are sentinels in the mucosal system ( 79 ). Neutrophils exert anti-bacterial effects through the release of their stored and newly synthesized mediators and the formation of neutrophils extracellular traps NETs ( 80 ). T H 17 cells produce IL-22 that promotes secretion of anti-microbial peptides such as β-defensins by epithelial cells.…”
Section: Gut Microbiota In Cvidmentioning
confidence: 99%